Reasons to be cautious about 'well-being' in economic development (and elsewhere). (2016) - Jenkins, Matt
'Well-being' is currently in vogue in policy-making circles in the Global North as a way of reconceptualising 'development'. This paper argues that its appearances are misleading. While the normative force of 'well-being' is accepted, what is being offered is a technocratic and reductionist programme which collapses 'well-being' into the statistical relation of a closed set of metrics. It is argued that 'well-being' as defined is a chaotic conception; not a concrete object but an evaluative state, and so such programmes necessarily fail to measure it. Further, it is argued that 'well-being' is already considered within economic development policy and that previous development initiatives would not have changed had well-being frameworks existed alongside them. It is suggested from this that 'well-being' merely provides a new way of describing economic development policy, without altering its fundamental logic or its inherent power relations.